2002
DOI: 10.1002/jrs.841
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of surface‐enhanced Raman spectroscopy response in gold–platinum core‐shell nanoparticles

Abstract: Colloidal gold particles (11.2 nm) were coated with platinum overlayers, resulting in bimetallic particles with 1-8 mol% Pt. These particles were characterized using electron microscopy, energy-dispersive x-ray spectroscopy and electrochemistry confirming the Au-Pt core-shell structure. The UV-visible spectra showed only minimal red shifts with increasing Pt content. The Raman spectra, on the other hand, changed dramatically with slight increases in Pt, resulting in a loss of appreciable surface-enhancement ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 59 publications
(47 reference statements)
2
25
0
1
Order By: Relevance
“…Furthermore, Flynn and Gewirth have reported that SERS-active points tend to be covered first when depositing other metals on gold nanoparticles. [14] Therefore, we believe that there is little pinhole interference in our experiment, because quite a large amount of copper was deposited on the gold nanoparticles (gold particles: % 12 nm; copper-coated particles: % 20 nm, as shown in Figure 1 of the Supporting Information).…”
Section: Resultsmentioning
confidence: 97%
“…Furthermore, Flynn and Gewirth have reported that SERS-active points tend to be covered first when depositing other metals on gold nanoparticles. [14] Therefore, we believe that there is little pinhole interference in our experiment, because quite a large amount of copper was deposited on the gold nanoparticles (gold particles: % 12 nm; copper-coated particles: % 20 nm, as shown in Figure 1 of the Supporting Information).…”
Section: Resultsmentioning
confidence: 97%
“…The enhancement factor of surface-enhanced Raman spectroscopy (SERS) is very sensitive to the physical and chemical nature of the Au surface [29]. To evaluate the interactions between the Au and IrO x in the current system, the SERS spectrum of IrO x [m]-Au were measured using the pure Au nanoparticles as a control.…”
Section: Resultsmentioning
confidence: 99%
“…Flynn and Gewirth prepared Au-Pt core-shell nanoparticles by first reducing Au 3+ and subsequently reducing tetrachloroplatinate ion on the gold particles [19]. The bimetallic sol has been used as substrates for surfaceenhanced Raman scattering (SERS) studies [19,20]. LizMarzan and Philipse have used optically transparent imogolite fibers to stabilize Au-Pt, Au-Ag, and Ag-Pt bimetallic hydrosols.…”
Section: Introductionmentioning
confidence: 99%
“…The polymer-protected particles have been used as catalysts for visible-light-induced hydrogen evolution reaction. Flynn and Gewirth prepared Au-Pt core-shell nanoparticles by first reducing Au 3+ and subsequently reducing tetrachloroplatinate ion on the gold particles [19]. The bimetallic sol has been used as substrates for surfaceenhanced Raman scattering (SERS) studies [19,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation